(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Neonatal care, particularly in resource-limited settings, requires strategies to optimize outcomes. Polyethylene covering has been proposed as a low-cost, effective intervention to improve thermoregulation and reduce infection rates in neonates. This systematic review aims to assess the impact of polyethylene covering on selected physiological parameters, infection rates, and clinical outcomes in neonates at tertiary care centers in Asia. Methods: A comprehensive search strategy was employed to identify relevant studies published in electronic databases, including PubMed, Embase, and Cochrane Library. Studies evaluating the use of polyethylene covering in neonates at tertiary care centers in Asia were included. Data on physiological parameters (such as temperature, heart rate, respiratory rate) Results: The initial search yielded a total of [142] studies, of which [06] met the inclusion criteria. The included studies varied in design, sample size, and outcome measures. Overall, polyethylene covering demonstrated a positive effect on selected physiological parameters, including improved temperature regulation and stability in neonates. Moreover, a trend towards reduced infection rates was observed in neonates receiving polyethylene covering compared to standard care. Conclusion: Polyethylene covering appears to be a promising intervention for improving physiological parameters. Further well-designed randomized controlled trials are warranted to elucidate its impact on clinical outcomes and establish guidelines for its implementation in neonatal care settings.